Physical characterization of clove oil based self Nano-emulsifying formulations of cefpodoxime proxetil: Assessment of dissolution rate, antioxidant & antibacterial activity - Amulya Jindal; Anoop Kumar (OpenNano, 2022)
Cefpodoxime proxetil (CPD) is a broad-spectrum cephalosporin widely indicated in respiratory tract infections like pneumonia. CPD is a BCS class IV drug with the constraint of low bioavailability attributable to its poor aqueous solubility (10µg/ml) and impaired permeability. Clove oil (CO) acts as a lipophilic additive for lipid-based delivery systems designed to facilitate dissolution characteristics of poorly soluble drugs, modulating drug permeability as well as stability against oxidation. The present work aims to improve CPD solubilization by developing CO-based fully dilutable self nano emulsifying formulation (SNF), and assessment of its antibacterial and antioxidant potential. The existence of nanoemulsion domains was tracked from ternary phase diagrams plotted between CO, Tween 20/PEG400 to act as oil phase, surfactant/co-surfactant (Smix) respectively at weight ratios 1:1, 1:2, and 2:1 whereas aqueous phase acted its tertiary component. Two subsets of SNF formulations coded as (DAO1-DAO5) and (DAM1-DAM3) were prepared and assessed for antioxidant and antibacterial activities respectively, along with their naive CO-counterparts (AO1-AO5) and (AM1- AM5) respectively. Physical characterization revealed SNFs were droplet size range 35-170nm, conductivities in the range 200-500uS/cm, and RI values in 1.361-1.429. The dilution-induced microstructure transition effect was observed in SNF with the addition of an aqueous phase as its oil-continuous domain transformed into water-continuous via bi-continuous structure formation as interpreted from conductivity and refractive index data. In-vitro dissolution characterization of SNF formulation exhibits a quick CPD release pattern in comparison to control in phosphate buffer at pH 6.8 and HCl buffer at pH3.0. SNF produced significant differences in the CPD release characteristics measured at different pH conditions in comparison to controls. These observations are plausible in terms of drug solubilization effect since SNFs possess a high proportion of surfactant and produce interfacial action on CO and CPD. Antioxidant activities in DAO and AO at CO 20, 40 & 100µg/ml levels were significantly different from controls as measured using the DPPH method. Comparison of antibacterial activity of DAMs against E. coli, B. subtilis, Enterobacter species, and S. aureus (scheme-II) vs CPD suspension or its coarse emulsion or even naive CO counterpart were statistically different and minimum inhibitory concentration of CPD was reduced in SNF formulations. These differences were well corroborated in the data exhibited in zones of inhibition studies. CO-based SNFs produced significantly improved dissolution characteristics of poorly soluble drugs like CPD and potentiated the antibacterial and antioxidant activities. Developed SNFs could be employed as Self nano emulsifying drug delivery systems (SNEDDS) for BCS class IV drugs.